Becoming an Efficient Reader: A Proposal for a School Curriculum - Gaona G Esperanza; Suárez Laura Isabel; González Hilma Cristina (Universidad Nacional de Colombia, 2001)
Reading should be the cornerstone of a school's curriculum in order to build up the other skills. Despite the fact that reading tends to be an obligation and a hard task, it should be seen as a fun activity which will extend the student's knowledge of the world. Reading efficiently in volves not only understanding, speed and fluency, but also the application of the student's knowledge, thus promoting critical thinking. That is to say, the "ability to reach sound conclusions based on observation and information". Due to the importance of acquiring reading skills in a foreign language, we see the necessity to stimulate students toward becoming efficient readers. That means avoiding word by word reading (Williams: 1984), and developing students' abilities to understand and comprehend a text and to read fluently